The Trans-Afghanistan Gas Pipeline as a Factor of Afghanistan’s Integration into the Greater East Asia: Comparative Analysis of Arguments Pro et Contra - Yuriy Pavlovich Laletin (Сравнительная политика, 2015)
The article focuses on a project of Trans-Afghan gas pipeline and its role in the future development of Afghanistan and the Greater East Asia. The author analyzes the historical stages of the project and challenges to its realization, as well as the current situation in Afghanistan aggravated by the fighting of the Taliban and warlords, drug trafficking, terrorist threat and ethnic conflicts. However, one of the main obstacles to the realization of the infrastructural plan is a competition between projects of neighboring countries.